Perlindungan Hukum terhadap Konsumen oleh Perusahaan Pembiayaan Berdasarkan Undang-Undang Nomor 8 tahun 1999 Tentang Perlindungan Konsumen - Suyadi Suyadi; Wiwik Yuni Hastuti; Sulistyandari Sulistyandari; Muksinun Muksinun; Sukirman Sukirman (Universitas Muhammadiyah Purwokerto, 2022)
AbstractThis research is entitled “Legal Protection of Consumers by Financing Companies Based on Law Number 8 of 1999 concerning Consumer Protection. The problem studied in this research is the legal protection for consumers by finance companies based on Law Number 8 of 1999 concerning Consumer Protection. The research method in this study uses a normative juridical approach. The results of the study were analyzed using a qualitative normative analysis method. The study results show that consumers have their rights protected, especially in Article 4 letters g and h of Law Number 8 of 1999 concerning Consumer Protection. This study concludes that business actors based on the decision of the Consumer Dispute Settlement Body Assembly to carry out the obligations as stipulated in Article 7 letter (a) of Law Number 8 of 1999 concerning Consumer Protection which determines the responsibilities of business actors. In this case, are Financing Companies must have good intentions in carrying out their business activities and implementing Article 19 of Law Number 8 of 1999 concerning Consumer Protection.Keywords: Legal Protection, Consumer Protection, Financing Company